PENGARUH MACHIAVELLIAN, TANGGUNG JAWAB SOSIAL, DAN PREFERENSI RISIKO TERHADAP KEPUTUSAN ETIS KONSULTAN PAJAK - Ng, Suwandi; Lukman, Lukman; Tanzil, Wenny Yuliana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this research was to investigate the relationship between machiavellian, social responsibility and risk preference on the ethical decision of tax consultants. The type of this research was explanatory research with quantitative approach. This research used theory of reasoned action and theory of moral development. The survey method was conducted on this research by distributing questionnaires to the respondents to obtain datas. 64 samples were collected from tax consultants who joined the Ikatan Konsultan Pajak Indonesia (IKPI) organization in Makassar, Manado and Denpasar with the total population of 272 consultants. The result of this research showed that machiavellian was negative and significantly affect the ethical decision of tax consultants, social responsibility was positive and not significantly affect the ethical decision of tax consultants and risk preference was positive and significantly affect the ethical decision of tax consultants. Determination coefficient test showed that machiavellian, social responsibility and risk preference gave affect of 39,5% on tax consultants ethical decision.